3D hydrogel platform with macromolecular actuators for precisely controlled mechanical forces on cancer cell migration - Bohan Li; Qingyu Fu; Yan Lu; Cheng Chen; Yingshuai Zhao; Yuanfeng Zhao; Minghui Cao; Wei Zhou; Xiaoliang Fan; Xiaoyu Jiang; Peng Zhao; Yijun Zheng (Nature Communications)
Abstract Mechanical forces play a critical role in regulating cancer cell behavior, particularly during metastasis. Here we present a three-dimensional hydrogel platform embedded with near-infrared-responsive macromolecular actuators that enable precise mechanical stimulation of specific integrin subtypes in cancer cells. By leveraging this system, we investigate how different force parameters—magnitude, frequency, and duration—affect the migration and invasion of ovarian cancer cell spheroids, focusing on the integrins αvβ3 and αvβ6. We find that mechanical stimulation enhances collective invasion at early stages and triggers a mesenchymal-to-amoeboid transition during later migration, especially when high-frequency, large-amplitude forces disrupt αvβ3-ligand interactions. In contrast, cells engaging αvβ6—through higher-affinity binding—show limited transition under similar conditions. Molecular simulations support these findings by revealing the underlying mechanics of integrin-specific responses. This 3D hydrogel platform provides a powerful tool for studying mechanotransduction in cancer cells and offers potential insights for developing targeted cancer therapies.